Modulation of Respiratory TLR3-Anti-Viral Response by Probiotic Microorganisms: Lessons Learned from Lactobacillus rhamnosus CRL1505 - Kitazawa, Haruki; Villena, Julio (Frontiers in Immunology, 2014)
Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract illness in infants and young children. Host immune response is implicated in both protective and immunopathological mechanisms during RSV infection. Activation of Toll-like receptor (TLR)-3 in innate immune cells by RSV can induce airway inflammation, protective immune response, and pulmonary immunopathology. Understanding the interaction between RSV and its host is crucial for the development of novel therapeutic strategies as well as safe and effective vaccines. Several studies have centered on whether probiotic microorganisms with the capacity to stimulate the immune system (immunobiotics) might sufficiently stimulate the common mucosal immune system to provide protection in the respiratory tract. In this regard, it was demonstrated that some orally administered immunobiotics do have the ability to stimulate respiratory immunity and increase resistance to viral infections. Moreover, during the last decade scientists have significantly advanced in the knowledge of the cellular and molecular mechanisms involved in the protective effect of immunobiotics in the respiratory tract. This review examines the current scientific literature dealing with the use of immunobiotic strains to prevent viral respiratory infections. More specifically, the article discuss the mechanisms involved in the capacity of the immunobiotic strain Lactobacillus rhamnosus CRL1505 to beneficially modulate the immune response triggered by TLR3 activation in the respiratory tract and to increase the resistance to RSV infection in infant mice. In addition, we review the role of interferon (IFN)-γ and interleukin (IL)-10 in the immunoregulatory effect of the CRL1505 strain that has been successfully used for reducing incidence and morbidity of viral airways infections in children.